THE EFFECTIVENESS OF PUZZLE PLAYING THERAPY IN REDUCING ANXIETY IN PRESCHOOL CHILDREN WITH ACUTE RESPIRATORY INFECTIONS: A PRE-EXPERIMENTAL STUDY - Sofiatun, Umi; Nisa, Nafisatun; Lestari, Siti (Journal of Vocational Nursing, 2025)
Introduction: Acute Respiratory Infections (ARI) are a leading cause of morbidity and mortality in preschool children. Nebulizer therapy is effective for ARI, but it can cause anxiety in pediatric patients, which may hinder their cooperation and recovery. This study aims to evaluate the effectiveness of puzzle play therapy in reducing anxiety levels among preschool children with ARI undergoing nebulizer treatment. Methods: A pre-experimental study utilizing a one-group pretest-posttest design was conducted involving 23 preschool children diagnosed with ARI who received nebulizer therapy in the Children's Room A11 at SMC Telogorejo Hospital, Semarang, between March and April 2024. Anxiety levels were assessed pre- and post-intervention using the Taylor Manifest Anxiety Scale (TMAS), which has demonstrated validity (CVI score = 1.0, reliability = 0.89). Puzzle play therapy was administered alongside nebulizer therapy, and the data were analyzed through paired t-tests.Results: Most participants were 4-year-old males (47.8%) with a hospital stay of more than seven days (56.5%). Before the intervention, 73.9% of participants had severe anxiety (mean = 23.65). Following the intervention, 73.9% of participants reported moderate anxiety (mean score = 12.78), with no instances of severe anxiety. The statistical analysis showed a significant decrease in anxiety levels (p = 0.001). Conclusions: Puzzle play therapy effectively reduced anxiety in children during nebulizer treatment. This intervention can be implemented as a non-pharmacological approach to manage anxiety in pediatric patients during medical procedures. Further research should investigate its long-term benefits and applicability in various clinical settings.